Conditioning Factors of Late Payment of Trade Credit - Claudinê Jordão de Carvalho (BBR: Brazilian Business Review)
This article presents new evidence on the practice of financial delinquency of trade credits. The low level of punctuality in pa yments to suppliers can negatively affect the liquidity of the lender and be transmitted to all companies in the value chain, creating uncertainties in the business environment. The aim is to identify and analyse the factors responsible for delay in paymen t to suppliers. A survey with 554 brazilian companies located in the provinces of Minas Gerais and São Paulo enable application of the model of ordered logit regression analysis . T he dependent variable is the financial delinquency level of companies that d o or do not delay the payment of duties , and the independent variables are the demographic, financial , and operational inherent demand for financing and moral hazard. The results show that companies with more short - term debt s , beginner on its business acti vities , and that have a higher proportion of customers who pay their credit purchase on time are more likely to delay their obligations to suppliers.